Does Human Capital and Gender Equality Affect Economic Growth for Ten Province in Sumatera? - Sitti Retno Faridatussalam; Dinar Wahyuningrum; Clarissa Dyah Anggraini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Purpose – The abundance of human resources becomes a burden on a country. On the other hand, the abundance of natural resources is an advantage if the government can use it well. The efforts made by the government are to improve the quality of human resources, including three indicators, namely healthy living, education, and decent living standards. However, it is accompanied by problems regarding gender discrimination that often occurs in various countries; this discrimination is often experienced by women, ranging from being objects of exploitation, subordination, violence and discrimination in all sectors. This study aims to analyze the effect of the Human Development Index and Gender Development Index on economic growth and the distribution of economic growth in ten provinces on the island of Sumatra in 2018-2021.Methodology – This research uses Static Panel Data Regression analysis tool and economic growth mapping using ArcGISFindings – The results of this study show that life expectancy and Income per capita have a positive and significant effect on economic growth. Meanwhile, the Mean Year of School variables and gender development index do not affect economic growth. Based on the results of mapping the distribution of economic growth, the area with the highest economic growth is North Sumatra Province. Then the area that has the lowest economic growth is Bengkulu Province.Originality/Novelty – The novelty in this study is mapping the distribution of economic growth for ten provinces on Sumatera Island with the results of the constant effect of panel data regression output.Implications – This research is still limited to the role of human resource development on economic growth and has not examined other variables that can affect economic growth. So that future research can use a different point of view on human resource development on economic growth.